Penentuan Rute Terpendek Untuk Mencari Lokasi Terdekat Menuju Tempat Ibadah Di Kota Sukabumi Menggunakan Algoritma Dijkstra - Muhammad Refli Septian; Lelah Lelah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2020)
Sukabumi City is a region in West Java that is experiencing rapid development. Especially in the construction of places of worship. Places of worship, places of worship, places of worship are places used by religious people to worship according to religious teachings. A mosque is a house of worship for Muslims or Muslims, a mosque means a place of worship. The mosque is also the center of life of the Muslim community. Celebration activities for religious holidays. Lectures and learning of the Qur'an are often carried out in mosques. Even in the history of Islam, mosques also play a role in social activities to the military. As for the City of Sukabumi there are 20 Mosques. To make it easier to search for mosques in the City of Sukabumi with the large number of mosques in the city of Sukabumi by using a web-based application. The application of the Dijkstra algorithm in the process of determining the location of the mosque to be headed in Sukabumi City based on the distance to be taken by determining the shortest route so that it can help people who will worship in the City of Sukabumi especially for people who are not from Sukabumi City